Assessing the Effectiveness of Chemical Exposure Management Practices in Sierra Leone’s Mining Sector: A Case Study of Sierra Rutile Mines - Dumbuya, Ibrahim; Fofanah , Mohamed Syed; Tiah, Bockarie (International Journal of Scientific Research and Management (IJSRM), 2024)
This study assessed the effectiveness of chemical exposure management practices in Sierra Leone's mining sector, focusing on the Sierra Rutile Mining Company. Utilizing a case study research design with both quantitative and qualitative methods, the research involved 70 workers from various departments, including the Mineral Separation Plant, Water Treatment Plant, Central Workshop, Laboratory, and Safety Department. Data were collected through semi-structured questionnaires and analyzed using SPSS and Excel.The findings indicate that workers' awareness of chemical exposure risks is adequate but the implementation of the strategies to mitigate the chemical exposure risk, such as effective monitoring, supervision, continuous training and strict adherence to regulatory frameworks are inadequate and inefficient. The study also reveals a shortage of specialized chemical safety personnel and poor adherence to safety regulations by management. These conditions have contributed to severe health outcomes such as respiratory and dermal diseases, eye defects, heart issues, lung damage, kidney problems, skin rashes, and mental health issues.The research concludes that chemical exposure significantly impacts workers’ health, and current management practices are insufficient. Recommendations include enhancing employee training on chemical safety, providing timely safety information, enforcing strict safety leadership, and improving regulatory compliance. Additionally, the study advises the government to prioritize research to support policy development. Future research should focus on health risk assessments, chemical toxicity, and the economic impact of chemical hazards.